'Politically devastating passions': Romance and reality in the aesthetics of democracy. Issue 6 (20th April 2022) - Gibbs, Alexis
Abstract: To speak of democracy is often to speak less of a fact than of a hope. In his introduction to Democracy in America, Alexis de Tocqueville admitted that '… in America I saw more than America; I sought the image of democracy itself, with its inclinations, its character, its prejudices and its passions, in order to learn what we have to fear or to hope from its progress'. De Tocqueville recognised that democracy's success would rely on its constant promotion, the affirmation and revaluation of its terms and conditions, such that it sustains the investedness of its (voluntary) participants. This paper considers the work of Stanley Cavell as inheriting the tone of de Tocqueville's romantic will to democracy, particularly in the discovery of its analogous image in 'remarriage comedy'. I look first at the ways in which popular pictures of (in this case, American) democracy on film sustain an expression of hope for a better set of relations amongst equal and consenting participants, an expression that is identified as romantic in nature. By contrast, I will also discuss how representations of democracy's reality on screen—pictures that sit outside comfortable generic expectations, and reveal those moments in which interest in democratic participation or values has ebbed or is dormant—have as much to tell us about democracy's character as more idealist expressions of what it might be or become.